2019
DOI: 10.1021/acsnano.9b00201
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Doping To Enable Tunable and High-Performance Anti-Ambipolar MoTe2/MoS2 Heterotransistors

Abstract: van der Waals (vdW) p–n heterojunctions formed by two-dimensional nanomaterials exhibit many physical properties and deliver functionalities to enable future electronic and optoelectronic devices. In this report, we demonstrate a tunable and high-performance anti-ambipolar transistor based on MoTe2/MoS2 heterojunction through in situ photoinduced doping. The device demonstrates a high on/off ratio of 105 with a large on-state current of several micro-amps. The peak position of the drain–source current in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
97
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(102 citation statements)
references
References 45 publications
4
97
0
1
Order By: Relevance
“…In particular, the incorporation of atomically thin semiconducting materials into gate-tunable p-n heterojunctions results in an antiambipolar response with Gaussian transfer curves [28][29][30][31][32][33][34][35][36][37][38] . While this behavior has been used for analog signal processing 37,39 , logic devices 30,35,38 , and photodetectors 28,32,34 , the single-gated geometries used previously do not provide sufficient control over the Gaussian current-voltage characteristic to enable efficient neuromorphic functionality. Here, we report the scalable fabrication of dual-gated Gaussian heterojunction transistors (GHeTs) based on mixed-dimensional van der Waals heterojunctions 40 consisting of monolayer molybdenum disulfide (MoS 2 ) grown via chemical vapor deposition (CVD) and solution-processed semiconducting single-walled carbon nanotubes (CNTs).…”
mentioning
confidence: 99%
“…In particular, the incorporation of atomically thin semiconducting materials into gate-tunable p-n heterojunctions results in an antiambipolar response with Gaussian transfer curves [28][29][30][31][32][33][34][35][36][37][38] . While this behavior has been used for analog signal processing 37,39 , logic devices 30,35,38 , and photodetectors 28,32,34 , the single-gated geometries used previously do not provide sufficient control over the Gaussian current-voltage characteristic to enable efficient neuromorphic functionality. Here, we report the scalable fabrication of dual-gated Gaussian heterojunction transistors (GHeTs) based on mixed-dimensional van der Waals heterojunctions 40 consisting of monolayer molybdenum disulfide (MoS 2 ) grown via chemical vapor deposition (CVD) and solution-processed semiconducting single-walled carbon nanotubes (CNTs).…”
mentioning
confidence: 99%
“…As a result, the MVL operations were possible only under light irradiation in these systems. Wu et al have reported a nonvolatile memory effect on the MVL in a MoS 2 / MoTe 2 system, [27] where the UV light and writing voltage were used simultaneously to store the electrical charges at the interface. Common to these previous studies, the fact is that the light irradiation impacts mainly on the electrical charges at the interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…We have utilized another merit of organic semiconductors, namely their light absorption capability over the visible to ultra‐violet (UV) wavelength range. Recently, the effect of light irradiation on AATs has allowed new optoelectronic devices to evolve, [ 6,24–28 ] , e.g., the use of the photovoltaic effect to reduce driving voltage, [ 24,25 ] the light‐triggered ternary inverter, [ 6,28 ] and light‐induced double “on” states. [ 26 ] Although these studies have led to novel optical functionalities, systematic and controlled studies are required for an in‐depth understanding of the operation mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…These devices exhibited anti-ambipolar behavior, with inverted V-shaped transfer curves as opposed to typical V-shaped transfer curves of ambipolar field-effect transistors (FETs), and were from vdW heterojunctions composed of MoS 2 and semiconducting single-walled carbon nanotubes (SWCNTs) in 2013. [8] The reported heterojunction materials for NDR or NTC devices include 2D semiconductors that possess dangling bond-free high-quality interfaces, [9][10][11][12][13][14][15][16][17][18] organic semiconductors, [19][20][21][22][23] and hybrid material combinations. [8,[24][25][26][27][28][29] More recently, a number of ternary inverters that possess three logic states have been reported by using heterojunctions of 2D semiconductors and organic semiconductors as a promising application in digital logic circuits.…”
mentioning
confidence: 99%
“…[8,[24][25][26][27][28][29] More recently, a number of ternary inverters that possess three logic states have been reported by using heterojunctions of 2D semiconductors and organic semiconductors as a promising application in digital logic circuits. [10,[12][13][14]17,18,22,23] However, reliable and scalable low-cost device fabrication methods should be developed in order to utilize integrated MVL circuits in IoT applications such as wearable electronic devices. In this regard, both 2D and organic heterojunction-based devices are not wellsuited at the current stage, because most 2D heterojunctions were formed by stacking individual mechanically exfoliated 2D flakes, while the reported organic heterojunctions were formed only by capital-intensive vacuum processes.In this work, inkjet-printed ternary inverters are presented for the first time by employing n-type indium oxide (InO) and p-type SWCNTs to form p-n heterojunctions.…”
mentioning
confidence: 99%